Intraosseous Anesthesia Using Dynamic Navigation Technology - Jain, Sameer D.; Carrico, Caroline K.; Bermanis, Ido; Rehil, Sonali (Journal of endodontics, 2020)
This study presents a novel method to deliver intraosseous anesthesia using dynamic navigation technology. The study aimed to evaluate its safety and 3-dimensional (3D) accuracy in comparison to traditional freehand injection of intraosseous anesthesia. Six identical sets of 3D-printed surgical jaw models (TrueJaw; DELendo, Santa Barbara, CA) comprising simulated alveolar and dental anatomy with 54 interradicular sites were used in this study. The injection sites were equally distributed based on the range of the inter-radicular distance (ie, 1.5–2.5 mm, 2.5–3.5 mm, and 3.5–4.5 mm). A board-certified endodontist randomly completed intraosseous drilling at inter-radicular sites of varying distance using freehand technique and the Navident dynamic navigation system (ClaroNav, Toronto, Ontario, Canada) with the X-Tip system (Dentsply Sirona, York, PA). The rate of root perforation associated with inter-radicular distance was compared between the 2 groups using the Fisher exact test. Two-dimensional (2D) and 3D horizontal, vertical, and angulation discrepancies between the planned and dynamically navigated guide sleeves were digitally measured using superimposed cone-beam computed tomographic scans. Analysis of variance models were used to determine if the interdental distance was associated with the accuracy measures from the dynamic navigation system. The significance level was set at 0.05. The rate of root perforation was significantly higher for the freehand group than the dynamic navigation (22% vs 0%, P < .05). For dynamic navigation, the 2D entry deviation was 0.71 mm (95% confidence interval [CI], 0.56–0.87). The mean 2D horizontal deviation was 0.96 mm (95% CI, 0.79–1.14), and the mean 2D vertical deviation was 0.70 mm (95% CI, 0.55–0.84). The 3D deviation at the tip was on an average 1.23 mm (95% CI, 1.05–1.42). The overall 3D angular deviation was on average 1.36° (95% CI, 1.15–1.56). The inter-radicular distance was not significantly associated with any 2D or 3D discrepancies. Successful and accurate drilling of dynamically navigated intraosseous delivery occurred in 100% of injection sites irrespective of the inter-radicular distance. It was significantly safer in comparison to freehand intraosseous drilling to prevent injury of the roots of the adjacent teeth in close proximity.